AKUNTABILITAS PENGELOLAAN DANA DESA DI KOTA BANDA ACEH: KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, DAN TRANSPARANSI - Rosa, Indah Puspita; Jalaluddin, Jalaluddin; Abdullah, Syukriy; Batara, Gamal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to determine the effect of apparatus competence, community participation, and transparency on the accountability of village fund management in Banda Aceh City. This type of research is quantitative research using primary data from questionnaires distributed directly to 73 villages in Banda Aceh City. The respondents in this study were 180 village heads, village secretaries, and village treasurers in Banda Aceh City. The sampling technique uses the simple random sampling method. The data analysis method uses the SPSS application version 23. The results show (1) apparatus competence, community participation, and transparency simultaneously affect the accountability of village fund management in Banda Aceh City, (2) apparatus competence has a positive effect on the accountability of village fund management in Banda Aceh City, (3) community participation has a positive effect on the accountability of village fund management in Banda Aceh City, and (4) transparency negatively affects the accountability of village fund management in the City Banda Aceh.